Toposim: Wireless ad hoc network topology simulator - Trajanov, Dimitar; Mickova, B; Filiposka, Sonja; Grnarov, Aksenti (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2003)
An important task of an ad hoc network consisting of geographically dispersed nodes is to determine the characteristics of the topology which include connectivity, energy-effectiveness, throughput, and robustness to mobility. However, the widely used network simulators don’t support topology simulations that result in an evaluation of the quality of the network topology. Thus, in this paper, we introduce a newly developed wireless ad hoc network topology simulator – TopoSim, that can be used for the purposes of simulating a topology of an ad hoc network, including its dynamical changes caused by the node’s mobility, for the purposes of determining the main topology characteristics of the simulated network.
Keywords: ad hoc networks, topology characteristics, simulation, simulator